Role of Microfinance in Poverty Alleviation with Special Reference to District Aligarh (India) - Nasir, Dr. Sibghatullah; Shajar, Dr. Syed Noorul; Khan, Saba (International Journal of Advanced Science and Technology, 2019)
Poverty is one of the main issues for developing countries especially for India. In this connection so many efforts have been done by several organizations viz. NGOs and other government institutions to alleviate poverty. Micro finance institutions have played a crucial role in poverty alleviation in many countries. In this paper the role of micro finance on poverty alleviation are analyzed by studying three factors like group’s age, loan amount and training for skill development as independent variables. Economic empowerment and employment generation have been taken as dependent variables. This paper is a humble attempt to emphasize the impact of micro finance on poverty alleviation in district Aligarh by using regression model. The paper is based on primary data and secondary data as well. A well structured schedule questionnaire was prepared to take the response of micro finance participants. The conclusion of the research paper is that micro finance is having a significant impact on poverty alleviation.